(untitled) (Indian Journal of Arid Horticulture, 2018)
Studies were conducted during 2015-17 at ICAR-Central Institute for Arid Horticulture, Bikaner in collaboration with ICAR-Central Potato Research Institute, Shimla to find out suitable potato cultivars for processing as well as for table purpose under North Western Rajasthan. Seven potato cultivars (Kufri Khyati, Kufri Garima, Kufri Chipsona-4, Kufri Pukhraj, Kufri Frysona, Kufri Surya and Kufri Jyoti) were raised under sprinkler irrigation as well as drip. Tuber yield varied significantly from variety to variety under both irrigation systems. Under sprinkler irrigation, Kufri Chipsona-4 gave higher yield (53.5 q/ ha) followed by Kufri Frysona (48.00 t/ ha) and Kufri Jyoti (46.5 t/ ha) while minimum yield was observed in Kufri Pukhraj (33.9 t/ ha) and Kufri Khyati (38.8 t/ ha). Kufri Garima and Kufri Surya gave intermediate yields (43.0 and 39.9 t/ ha), respectively. However, under drip irrigation, Kufri Frysona gave higher yield (43.5 t/ ha) followed by Kufri Chipsona-4 (42.9 t/ ha) and Kufri Garima (37.5 t/ ha) and minimum yield was observed in Kufri Pukhraj (20. 0 t/ ha). Kufri Frisona gave higher medium sized tuber yield (14.6 t/ ha) followed by Kufri Surya (11.2 t/ ha) and Kufri Chipsona-4 (9.30 t/ ha) under sprinkler irrigation while, under drip irrigation Kufri Jyoti produced the highest medium sized tuber yield (11.7 t/ ha) as compared to other. Thus, processing varieties Kufri Chipsona-4 and Kufri Frysona were found suitable and proved to possess high dry matter content and were the most efficient varieties in the arid region while for table purpose Kufri Garima and Kufri were found suitable for processing and table purpose, for cultivation in north western Rajasthan